DECREASED TUMOUR NECROSIS FACTOR ALPHA (TNF-Α) IN SERUM OF PATIENTS WITH ACHILLES TENDINOPATHY: FURTHER EVIDENCE AGAINST THE ROLE OF INFLAMMATION IN THE CHRONIC STAGE. Issue 7 (11th March 2014) - Gaida, J; Alfredson, H; Forsgren, S; Cook, J
Abstract : Background: Altered expression of several cytokines and growth factors has been shown in biopsies of tendinopathy tissue. Biopsy studies are however challenged by capacity to obtain i) healthy tissue for comparison, ii) multiple samples to monitor cytokine dynamics, and iii) tissue from recent onset tendinopathy. An alternative is to study cytokines in blood samples. Whether cytokines in blood samples reflect tissue levels and the degree of tendinopathy is unknown. Objective: To measure serum concentration of six cytokines and growth factors suggested to have a role in tendon response to load among individuals with chronic Achilles tendinopathy and controls. Design: In this cross-sectional study, serum cytokine concentrations were measured from fasting blood samples on the BioPlex-200. Setting: Sports Medicine Unit, Umeå University. Participants: Participants were recreationally active individuals. Achilles tendinopathy (n=22) was diagnosed on clinical criteria and confirmed with ultrasound examination. The control group (n=10) had no history of tendon pain and had normal ultrasound findings. Independent variables: Serum concentration of tumour necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β), basic fibroblast growth factor (bFGF), platelet derived growth factor BB (PDGF-BB), interferon gamma (IFN-γ), and vascular-derived endothelial growth factor (VEGF) were the independent variables. Main outcome measurements: A diagnosis of Achilles tendinopathy (yes/no) was defined as the key outcome variable prior to data collection. Results: TNF-α concentration was lower in the tendinopathy group than the control group (P=.018); there were no other group differences. Conclusions: The observations indicate a lowering of the TNF-α concentration in the chronic phase of Achilles tendinopathy. As TNF-α levels are elevated in chronic inflammatory conditions, this reinforces that chronic Achilles tendinopathy is not an inflammatory disorder. Collecting a blood sample to study disease biomarkers leaves the tendon intact and therefore this design can be used to study cytokine dynamics with multiple sampling during disease progression and recovery.